Новая политика в отношении Вьетнама? Государственное управление Российской Федерации и реализация свободного торгового соглашения с Вьетнамом - ФедоровНиколай (Вопросы государственного и муниципального управления, 2018)
The Free Trade Agreement between the Eurasian Economic Union and Vietnam, signed in May 2015, has special political significance for both Eurasian integration and Russian-Vietnamese relations. However, an important issue is the problem of the efficiency of this agreement for the Russian economy. Despite the high level of political contact between Russia and Vietnam, their economic interaction is still at a relatively low level. But at the same time, the FTA is often considered to be a factor that can impact positive influence on economic cooperation between Russia and Vietnam. Focusing on the political meaning of the EAEU-Vietnam FTA, the aim of the article is to research the role of Russian state administration in the development of the free trade zone. The author analyzes the activity of Russian state structures (the Ministry of Economic Development, the Russian Export Center, the Trade Mission in Vietnam etc.) in terms of their assistance in the realization of the FTA, considers the results of their work and makes conclusions on the future prospects of the free trade zone between the EAEU and Vietnam. The Russian state administration has taken part in organizing different events (official summits, roundtables, exhibitions, business forums), assisted in communication between the Russian and Vietnamese business communities, and provided information support. But despite some achievements by the FTA, there are still a lot of unsolved problems and so interaction between state administration and business seems to be a necessary condition for the improvement of Russian-Vietnamese economic cooperation.